Pengaruh Return On Equity, Debt to Equity Ratio, Basic Earning Power, Economic Value Added dan Market Value Added Terhadap Return Saham - Jie Lydia Irawan (Universitas Kristen Maranatha, 2021)
In investing, investors expect stock returns from their investment, using Return On Equity (ROE), Debt to Equity Ratio (DER), Basic Earning Power (BEP), Economic Value Added (EVA), and Market Value Added (MVA), which are expected to provide an overview and information about the company to be invested in. The purpose of this study was to examine the effect of ROE, DER, BEP, EVA, and MVA on stock returns.The test uses multiple linear regression using a sample of 33 active companies that are always listed on the LQ45 index in 2017-2019 period. The partial test results show that DER and BEP have an effect on stock returns, while ROE, EVA, and MVA have no effect on stock returns. Simultaneous test results obtained ROE, DER, BEP, EVA, and MVA have an effect on stock returns. Investors should pay attention to the DER and BEP of the company because these variables have an effect on stock returns. Keywords: Return On Equity, Debt to Equity Ratio, Basic Earning Power, Economic Value Added, Market Value Added,and Stock Return.